Evaluation of posterior superior alveolar artery using cone-Beam computed tomography in the Indian population: A retrospective study - Isha P Kale; Amit A Mhapuskar; Pradnya Karmarkar; Muskan Jhawar; Darshan R Prasad Hiremutt; Abhijeet Jadhav (Wolters Kluwer Medknow Publications, 2023)
Background: The posterior superior alveolar artery (PSAA) is commonly encountered during various surgical procedures such as sinus lift, osteotomy, and Le Fort I fractures. Objective: This study was undertaken to evaluate the anatomical relationship of PSAA with the alveolar crest using cone-beam computed tomography (CBCT). Methods: This retrospective, analytical, comparative study was conducted on 192 CBCT scans (=384 PSAA notches) of dentulous patients above the age of 20 years. The position, diameter, and distance of the artery to the alveolar crest in the first molar region were evaluated bilaterally, in different age groups and among both genders. Results: In our study, the position and dimension of the notch of the PSAA were statistically significant with respect to age. The distance of the artery to the alveolar crest was statistically significant with respect to age and gender. No side differences were seen. Conclusion: The distance of the PSAA to the alveolar crest in the first molar region was approximately 14.62 mm in the Indian population. Hence, surgical procedures involving this artery should be conducted at a distance of <14 mm to avoid hemorrhage. CBCT can be used to evaluate the position and path of the PSAA accurately.